The advent of plant cells in bioreactors - Verdú-Navarro, Fuensanta; Moreno-Cid, Juan A.; Weiss, Julia; Egea-Cortines, Marcos (Frontiers in Plant Science, 2023)
Ever since agriculture started, plants have been bred to obtain better yields, better fruits, or sustainable products under uncertain biotic and abiotic conditions. However, a new way to obtain products from plant cells emerged with the development of recombinant DNA technologies. This led to the possibility of producing exogenous molecules in plants. Furthermore, plant chemodiversity has been the main source of pharmacological molecules, opening a field of plant biotechnology directed to produce high quality plant metabolites. The need for different products by the pharma, cosmetics agriculture and food industry has pushed again to develop new procedures. These include cell production in bioreactors. While plant tissue and cell culture are an established technology, beginning over a hundred years ago, plant cell cultures have shown little impact in biotechnology projects, compared to bacterial, yeasts or animal cells. In this review we address the different types of bioreactors that are currently used for plant cell production and their usage for quality biomolecule production. We make an overview of Nicotiana tabacum, Nicotiana benthamiana, Oryza sativa, Daucus carota, Vitis vinifera and Physcomitrium patens as well-established models for plant cell culture, and some species used to obtain important metabolites, with an insight into the type of bioreactor and production protocols.